Pendeteksian Tepi Citra untuk Menentukan Kualitas Beras Berdasarkan Jenis Menggunakan Metode Laplacian of Gaussian - Jaberes Nababan (KLIK: Kajian Ilmiah Informatika dan Komputer, 2020)
Rice is a staple food for most Indonesian people. Rice consumption in Indonesia is increasing every year along with the increasing population of Indonesia. The high dependence of the Indonesian people on rice will be a problem if the availability of rice cannot be fulfilled. The Laplacian of Gaussian method can detect edges more accurately especially on steep edges. In addition, it can be said to be more accurate because it can reduce the appearance of false edges, because the image is filtered first with a Gaussian function. This Laplacian method has been widely implemented to analyze various problems. The purpose of this study is to detect the edges of rice images and determine their quality more accurately using the Laplacian of Gaussian method